Electrooptical effect in the magnetic colloid near the electrode surface - Konstantin Valer’evich Erin (Наука. Инновации. Технологии)
In the article a physical model of the effect of changing the transparency of the colloidal solution of nanoparticles in kerosene by pulsed electric field, taking into account the effect on the optical parameters of the effect of space charge near the electrode and the concentration wave of magnetic nanoparticles. It is shown that for the first correct explanation of the features of optical effects in the near-electrode region of the need to account polydispersity of nanoparticles and their aggregates.